Por que ser licenciado em Ciências Sociais? Um estudo sobre os significados da escolha profissional - Xavier, Patrícia Silva (2016)
The study seeks to understand the meanings of choice by the students, by the Course mode in the course of Social Sciences at the Federal University of Ceará between the years 2002 to 2008. This time corresponds to the period in which sociology discipline was not part the compulsory curriculum of high school, having been built only in 2008, with the approval of the National Law No. 11684/08 which ensured his return. I intend to understand how the students conducted their trajectories in a period that was not an institutionalized professional field, I also seek to understand how the course of Social Sciences in the mode degree was organized, if there were incentives to choice or discussions concerning the teaching profession, their areas of operation and what the prospects for training presented in politicalpedagogical projects of degree course. The work sets up an analysis of the speeches of the graduates, using qualitative research techniques.The answers will be sought through semi-structured interviews with egresses and documentary research with analysis of documents (political pedagogical project, syllabus and disciplines content). It was used authors discussing Degree and sociology in high school. The survey results identify the mishaps in building this career because at that time there was no incentive policies. It was concluded that the students graduated during this period the degree does not reach half of the trainees in the Social Sciences course.